Antecedents to trust and link with participation in three local councils in the state of Selangor / Farah Adilla Ab Rahman - Ab Rahman, Farah Adilla (2019)
The Malaysian government system is divided into three levels, namely the federal government, the mute governments and the local governments. The local government is deem the closest to the people. In recent decades, there is a worldwide decline of the trust for the governments by the citizens. However, the level of trust by citizen is different across the three levels of government which are the federal government, the state governments and the local governments. In addition, trust in the local government is more significant because it involves activities and programs that are important to the citizens. Resident participation in the local government is an effective method to reduce the level of resident distrust and to educate them about governmental activities. Hence, this research determine how residents view trust towards the local government, to explore antecedents of trust in the local government, to ascertain the link between trust and participation and to formulate an inductive model of trust in the local authority. This study, utilises qualitative research design. The local government areas that were involved are the Petaling Jaya Municipal Council area (pilot case study), the Shah Alam City Council area, the Subang Jaya Municipal Council and Kuala Selangor District Council area. The selection of the respondents were based the active participation in resident association, citizenship and the years that they had lived in that area. Based on the analysis and discussion of the study, it shows that trust encourages residents to participate. Moreover, half of the respondents agreed that when residents distrust the local government, they will indeed not participate. The residents’ level of trust in the local government also has an impact on how often they participated. If they had trusted the local government, they will participate often.